Artificial Regulation Effect of Plant Retardants on Leaf Anatomical Characteristics of Elaeagnus Angustifolia - Zhang, Chao; Li, Wanjiao; Gao, Yong; Xu, Zhengzheng; Tian, Xiaoning (Frontiers in Environmental Science, 2022)
Aims: In order to explore the adaptation mechanisms of Elaeagnus angustifolia to the arid environment in desert areas under the treatment of artificial plant retardants. The test used Elaeagnus angustifolia Linn. to investigate artificial regulation by using retardants of paclobutrazol, paclobutrazol+adhesive and chlormequat based on multi-factor and multi-levels. Methods: Latin Square design of L9(34) was used design the experimental treatment combinations. Leaf morphological and structural characteristics by paraffin section method was used to explain the effect of different treatment and its combinations. Results: The leaves of Elaeagnus angustifolia were iso-petalous with obvious stellate epidermal fuzzes on the upper epidermis. The palisade tissue was well-developed and tightly arranged. The T1-T9 treatment significantly increased leaf thickness. Conversely, leaf length and width showed a retarded growth effect, while leaf growth developed as an elongated type after application.(3) After plant retardant control, the upper epidermal thickness, palisade tissue and spongy tissue thickness of the leaves showed a significant trend to increase, at the same time, the number of xylem rows increased and the number of cells per row increased and arranged closely, meanwhile, there is a synergistic evolution phenomenon among the indexes. (4) The best treatment combination of plant retardant to regulate the leaf configuration of plant is A3B2C1D2, i.e. select the concentration of 600mg/L of PP333, using the root application + leaf application method for 2 applications. Conclusions:The study showed that plant retardants improved the ability of plants to resist external environmental stress by reducing leaf area, increasing leaf thickness and epidermal thickness, promoting the development of mesophyll and vein structure in order to improve water retention capacity and prevent transitional transpiration.